Comparative study of commercial 4-methylumbelliferyl-beta-D-glucuronide preparations with the Standard Methods membrane filtration fecal coliform test for the detection of Escherichia coli in water samples. - Clark, D L (1991)
The performance capabilities of two commercial 4-methylumbelliferyl-beta-D-glucuronide preparations were evaluated for the detection of Escherichia coli from water samples. Eighty-three water samples were collected from a treated water reservoir, and 32 samples were collected from untreated surface water. There was a statistically significant difference between the two commercial preparations compared with the Standard Methods membrane filtration fecal coliform (MFC) method for the detection of E. coli from treated water samples. However, there was no difference between the two methods and the MFC test for E. coli detection from the untreated surface water samples. The disagreement between the two commercial products and the MFC method was primarily due to the occurrence of false-negative results with the two commercial products. The data indicate that the occurrence of false-negative samples could be attributed to impaired substrate specificity and sensitivity of the two tests for E. coli detection. There was no apparent relationship between the occurrence of false-negative results and heterotrophic plate counts in samples.